Magnetic Relaxation in Nanocrystalline Systems: Linking Monte Carlo Steps with Time - Altbir-Drullinsky, D (WALTER DE GRUYTER GMBH, 2022)
The magnetic relaxation of a noninteracting two-dimensional ensemble of magnetic nanoparticles is simulated as a function of temperature using a Monte Carlo technique. By properly fitting the decay of magnetization using real parameters it is possible to make, at any finite temperature, a clear correspondence between Monte Carlo steps and time measured in seconds. The results allow one to visualize the intrinsic problems related to the simulation of nonequilibrium systems, and to understand the limits and range of validity of a particular system.